PEMBANGUNAN SISTEM INVENTARISASI PERANGKAT TEKNOLOGI INFORMASI DAN KOMUNIKASI BERBASIS WEB (Studi kasus : disduk capil kabupaten Cianjur) - Nur Alamsyah; Luky Lukman (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2020)
Information technology has developed rapidly as the development of globalization has many applications that have been built to alleviate manual work to be automatic, controlling population of inventory items is quite complicated because of the distance between sub-districts in one district, so that frequent errors in checking are not efficient because in conducting activities checking inventory items still uses the manual method of checking one by one in each sub-district so that it takes a long time to make a report. The system created will be used to simplify the work, including in the activity of checking goods because it is able to simplify and present information that is relatively long, the function of a self-made system is to convey information and get a quick response and facilitate checking of official goods inventory. By building applications that manage data or official inventory information, making work easier. The application is online which will make it easy to check and report inventory items. Keywords : Controlling System, Administration Service, Citizenship, Web Applications